An automatic waste cleaning system in shrimp ponds with digital image processing using the internet of things: - Zainullah, Zainullah; Waluyo, Waluyo; Taufik, Mochammad (Jurnal Jaringan Telekomunikasi, 2023)
Super intensive shrimp pond wastewater with a stocking density of 750-1,250 individuals/m2 contains an average total suspended solids (TSS) of 798-924 mg/L, dissolved organic matter (BOT) of 81,227-88,641 mg/L; total nitrogen (TN) 9.8389-14.4260 mg/L; and total phosphate (TP) 7.8770-11.8720 mg/L. This value has exceeded the threshold limit of the permissible pond wastewater standard so it has the potential to hurt the environmental quality of water bodies receiving the waste load. making a more intensive vannamei shrimp farming pond cleaning system using turbidity sensors to read turbidity in shrimp farming ponds and ultrasonic sensors as readers of the water level in shrimp farming ponds and using a camera to detect the presence of foam waste in shrimp farming ponds and the Raspberry Pi microcontroller as a center system control on control devices and monitoring of all sensors then the output data will activate the drainage of leftover shrimp feed and shrimp waste from drainage to disposal using PVC pipes and automatic faucets that are driven using DC power window motors. The Internet of Things (IoT) automatic system in the construction of a waste cleaning device for shrimp ponds was built using a turbidity sensor that can detect the level of turbidity in water with an accuracy of 0.51%. The need for additional water in the pond is assisted by an ultrasonic sensor which provides information to the water pump with an average accuracy of 0.56%. To detect foam waste using a webcam camera as a foam detector.